Ankara's economic policy dilemma: Europe's options for economic and security cooperation with Turkey - Yasar Aydin (Stiftung Wissenschaft und Politik (SWP), 2024)
Turkish President Recep Tayyip Erdoægan began his third term in May 2023 with the appointment of Mehmet ðSimðsek as finance minister and the business executive Hafize Gaye Erkan as governor of the central bank. Both are widely acknowledged and experienced proponents of orthodox economics. The effect of their appointment was to return Ankara to an orthodox economic course. However, the shift in monetary policy was not backed up by structural reforms and the recovery has been meagre. Inflation remains rampant and the currency continues to fall; unresolved economic challenges create economic and political instability and could weaken the country's security - in particular in light of Russia's ambitions to expand its influence in the region. The consequences for the EU would be enormous. Turkey needs economic and security cooperation with Europe to secure stability without legitimising the regime's autocratic course.the dilemma between geopolitics and integration policy, the European Commission is currently developing ideas about how new members can be integrated step by step.
Keywords: 320; Turkey; Recep Tayyip Erdoægan; Mehmet ðSimðsek (finance minister); Hafize Gaye Erkan (governor of the central bank); monetary policy; inflation; Russia’ s ambitions; EU; economic and security cooperation; NATO